Appropriate Scaffolding Format in Physics Learning through Lesson Study on Improving Students' Problem Solving Skills - Saputro, Sigit Dwi (LPPM Undiksha, 2023)
Each learning material has a different form of scaffolding to achieve maximum mastery. This study aims to analyze the differences in students' problem solving on temperature material due to scaffolding and find the right form of scaffolding on temperature material through lesson study on the achievement of students' problem solving skills. This type of research is a pre-experiment design with a replication class. The instruments used in this research are temperature conversion essay test and learning reflection sheet. The analysis of this study used SPSS Version 17. The instrument of this research is an essay test of 5 questions that are valid and reliable with an Alpha Cronbach value of 0.97 and a learning reflection sheet. The improvement of problem solving ability was analyzed based on the Gain-score. The provision of scaffolding has an impact on the difference in improving students' problem solving skills in temperature material through lesson study. The form of scaffolding that can improve problem solving skills on temperature material is the provision of teaching materials equipped with menemonic technique approach, pauses are made to open questions during the learning process, the need for U-shaped seating rules to increase interaction in one group. Suggestions for this research need to be done interaction between groups and making evaluations with digital applications to measure individual abilities with fast results.